2021
DOI: 10.1017/jfm.2020.1075
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the jet wiping process via integral models

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 94 publications
(137 reference statements)
3
25
0
Order By: Relevance
“…2019), the jet-wiping (or air-knife) coating process in which impinging jets of air are used to control the thickness of a fluid film on a moving substrate (Barreiro-Villaverde, Gosset & Mendez 2021; Mendez et al. 2021), while a film of fluid on a rotating cylinder in an airflow is a key component of a recently proposed method for applying pesticides to crops using minimal amounts of chemical and with minimal drift (Newell & Viljoen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2019), the jet-wiping (or air-knife) coating process in which impinging jets of air are used to control the thickness of a fluid film on a moving substrate (Barreiro-Villaverde, Gosset & Mendez 2021; Mendez et al. 2021), while a film of fluid on a rotating cylinder in an airflow is a key component of a recently proposed method for applying pesticides to crops using minimal amounts of chemical and with minimal drift (Newell & Viljoen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the long-wavelength nature of the undulation is reminiscent of interface instabilities in gravity-driven falling films [9][10][11] , several works 5,12,13 have shown that these do not result from an intrinsic instability of the liquid coat. On the other hand, it has been recently shown 14,15 that the liquid film is sensitive to jet disturbances such as pulsation and oscillations, if these occur at sufficiently low frequencies. The present work analyzes the origin of jet disturbances and their impact one the coating film.…”
Section: Arxiv:210316116v1 [Physicsflu-dyn] 30 Mar 2021mentioning
confidence: 99%
“…As of today, the only tools available to analyze some of the mechanisms at the origin of the undulation in galvanizing conditions are simplified integral models, recently extended by Mendez et al 15 . These models were used to derive the response of the liquid film to a set of perturbations and identify, for various operating conditions, the range of frequencies yielding the largest disturbance amplification.…”
Section: Arxiv:210316116v1 [Physicsflu-dyn] 30 Mar 2021mentioning
confidence: 99%
See 2 more Smart Citations